Strategic Leadership in Shaping Religious Character: The Role of School Principals in Islamic Education - Yuliawati, Ayu; Hasanah, Aan; Zaldi, Ahmad; Jalaludin, Jalaludin; Saeki, Jeki (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study examines the strategic role of school principals in shaping students' religious character through institutionalized habituation management. The purpose of this study is to identify approaches to developing students' religious character, as well as implementation and evaluation strategies applied by school principals. This study uses a qualitative method with a case study approach, with data collection techniques through participant observation, documentation, and interviews. An interactive model is used in analyzing the data, and credibility, transferability, dependability, and confirmability tests are conducted to verify the validity of the data. The results show that structured habituation activities, such as school literacy, extracurricular activities, Al-Qur'an recitation, prayer, apperception, reflection, and the application of the 5S method (smile, greeting, greeting, politeness and courtesy) can contribute significantly to the formation of students' religious character. In addition, activities such as K3 (cleanliness, beauty, order), Yasin recitation, weekly muhadhoroh, congregational prayer, and Juz Amma memorization also play a role. The principal's determination of school policies is a determining factor in the success of this program. The implications of this research provide practical contributions to the development of structured Islamic education management strategies and provide deeper insights into strategic leadership in values-based education.